Determination of the copy numbers of type A porcine endogenous retroviruses in domestic pigs and wild boars - R. B. Aitnazarov; N. S. Yudin; R. S. Kiril’chuk; N. N. Kochnev; S. P. Knyazev; M. I. Voevoda (Вавиловский журнал генетики и селекции, 2017)
Modern transplantology is in need of transplants. To solve this problem, the use of animal organs and tissues for grafting to humans (xenografts) has been proposed. However, the progress in this direction is hampered by the risk of zoogenous infection of recipients. With regard to economic and ethical criteria and to the anatomical and physiological similarity to humans, the pig is the best source of xenografts. The pig genome harbors type A porcine endogenous retroviruses (PERV), which can infect human cell lines in vitro. A population of Siberian minipigs was raised at the Institute of Cytology and Genetics just for xenografting. The goal of the present study is to analyze the copy numbers of PERV A in Siberian minipigs, their founder breeds Landrace and Large White, and wild boars. The copy numbers of PERVs have been determined by absolute measurement with SYBR Green dye. End-point dilutions of a sample with a known copy number have been used for reference. The PERV A copy numbers in standard samples of Siberian minipig DNA are 2.4, 3.6, and 4.9 per cell, which is consistent with data obtained by other scientists. Minipigs and wild boars show a significant difference in retrovirus copy numbers. Thus, the Siberian minipig genome has a considerable number of type A PERVs, conceivably pathogenic to humans. It is necessary to select animals with minimum PERV numbers in the genome for xenografting. The method of PERV A quantitation with SYBR Green allows detection of such animals and selection of Siberian minipigs for reduction of this index.